Engineered co-crystals as scaffolds for structural biology - Orun, Abigail R., author; Snow, Christopher D., advisor; Ackerson, Christopher, committee member; Kim, Seonah, committee member; Ho, P. Shing, committee member (Colorado State University. Libraries, 2022)
Biomolecules, like protein and DNA, serve as the foundation of life. The structure of biomolecules can give insight to their functions. X-ray crystallography is a cornerstone of structural biology, revealing atomic-level details of macromolecular structures. Even with advances in X-ray diffraction technology, haphazard and tedious crystal preparation remains the bottleneck of routine structure determination. An alternative to the crystal growth challenge is a scaffold crystal. Hypothetically, if one had a high-quality crystal already prepared with large enough pores for diffusion of a macromolecule, a biomolecule of interest could join the scaffold crystal for scaffold- assisted X-ray diffraction. An ideal scaffold crystal must be highly porous for guest addition, modular for installation of various guest molecules, and robust in changing solution conditions. A crystal with guest anchoring sites for post-crystallization guest addition may provide a high-throughput technique for guest DNA-binding protein structure determination. The overarching goal of this work is to design a novel scaffold crystal capable of scaffold-assisted X-ray crystallography. The scaffold crystals we designed are co- crystals of DNA and DNA-binding protein. In the co-crystal, the DNA serves as the anchoring point for guest DNA-binding guest targets while the protein acts as connective tissue to hold the DNA structure together. The scaffold co-crystal we engineered, Co-Crystal 1 (CC1), is the first example of a porous host crystal for DNA-binding guests. Ultimately, the expanded co-crystals may serve as a revolutionary figurative "lens" for routine structure determination. In addition to scaffold crystal development, we advanced methods to enhance scaffold stability and solution-independence, thereby augmenting the bioconjugation toolkit for crystals containing stacking DNA-DNA junctions. Specifically, we optimized a known bioconjugation technique, carbodiimide chemical DNA ligation, templated by crystals with stacking DNA junctions. Furthermore, crystal crosslinking chemistries were optimized to provide crystal strength at both the nanoscale and the macroscale. Post- crosslinking, co-crystal nanostructures were preserved as assessed using X-ray diffraction and co-crystal macrostructures were bolstered in harsh solution conditions. The crosslinking chemistry and protocol guidelines may advance the progress of DNA crystals and protein-DNA co-crystals utility in biomedical applications and structural biology. We are on the cusp of using designed co-crystals to host guest DNA-binding proteins for structural biology, bio-sensing, and bio-therapeutic delivery. Successful engineering of a designed porous co-crystal will open numerous application possibilities and scientific questions. For example, a future study could focus on quantifying guest protein diffusion rates and adsorption strength inside the porous scaffold crystals. The technology presented here may advance the study of DNA-binding proteins and advance our understanding of key proteins for cancer and disease.
Keywords: crosslinking; ligation; X-ray crystallography; DNA-binding protein; co-crystals; structural biology